DILEMA HUKUM PEMUTUSAN HUBUNGAN KERJA (PHK) DI PERBANKAN: ANALISIS PERSPEKTIF UNDANG-UNDANG KETENAGAKERJAAN DAN PERATURAN PERBANKAN - Didi Handono Syahputra; Lira Amelia; Nabilah Irwani; Nesya Aulia; Nikmah Dalimunthe; Sandi Sipahutar (widya balina, 2025)
This study examines the legal dilemmas in Employment Termination (PHK) within the banking sector, arising from the tension between Labor Law and banking regulations. A normative analysis reveals that termination practices are often caught in a conflict between the principle of worker protection and the bank's obligation to comply with prudential principles and maintain its financial health. The most critical points of friction lie in termination due to efficiency measures, serious disciplinary violations, and the clash between banking secrecy and the evidentiary process in the Industrial Relations Court. It is concluded that the lack of harmonization guidelines creates legal uncertainty, necessitating more concrete regulatory synergy between labor authorities and the Financial Services Authority (OJK) to achieve certainty and fairness for all parties involved.